(untitled) (Journal of Gender and Social Issues, 2018)
Media has played a significant role in revolutionizing women’s lives over a period of time. It has made the audiences to focus on the wants and needs of females through various modes of communication, including cinema. Feminist theorists like Mary Wollstonecraft, Elaine Showalter and many more, in this regard, have been trying to provide women with respect and recognition, which all human beings must possess, through their writings. They highlighted the importance of various gender roles performed by women in relation to males in patriarchal society. Their writings have made the female community to rethink about their ‘self’ from a radical perspective. Moreover, this has made women to have realization and acceptance of their abilities and intellect, challenging the set male norms regarding positioning of women. The role of modern feminists to let go male chauvinistic approach regarding positioning of women and explain the perceptive of early twenty.